Pros and Cons of Multimodality in AI Used by College Students - Lateef , Umnia Jamal; Ahmed , Imad Ibrahim; Hussein , Sara Khalil; Yasseen , Aws Abduljabbar; Ghalavandi, Hassan. (Journal of Ecohumanism, 2025)
Artificial intelligence’s (AI) incorporation of multimodality has revolutionized education by giving college students cutting-edge resources for communication, learning, and problem-solving. Richer interactions and more individualized learning experiences are made possible by multimodal AI, which integrates many input formats like text, graphics, speech, and video. Even while there are advantages like increased accessibility, creativity, and teamwork, problems like unequal access, ethical dilemmas, and cognitive overload still exist. This study examines the benefits and drawbacks of multimodality in AI as it relates to college students, offering insights into its educational implications and the necessity of ethical, well-balanced integration.